TWENTY YEARS OF INDEPENDENCE IN KAZAKHSTAN AND KYRGYZSTAN: WHAT IS MORE IMPORTANT— POLITICAL OR ECONOMIC DEVELOPMENT? - BAKAS UULU, Bakhtiar (CENTRAL ASIA AND THE CAUCASUS, 2011)
The dispute about what is more important, political or economic development, is like the philosophical discussions of what came first, the chicken or the egg. However, despite the ongoing debates, the answer, we think, is obvious: long-term and stable development of society is only possible with mutual agreement and complementarity, as well as parallel (joint) advancement of political and economic reforms. This is clearly shown by the 20 years of independence in Kazakhstan and Kyrgyzstan, two neighboring countries which chose different paths of development.